2017
DOI: 10.1136/bmjopen-2016-012901
|View full text |Cite
|
Sign up to set email alerts
|

Generic prognostic factors for musculoskeletal pain in primary care: a systematic review

Abstract: ObjectivesTo summarise the evidence for generic prognostic factors across a range of musculoskeletal (MSK) conditions.Settingprimary care.Methods and outcomesComprehensive systematic literature review. MEDLINE, CINAHL, PsychINFO and EMBASE were searched for prospective cohort studies, based in primary care (search period—inception to December 2015). Studies were included if they reported on adults consulting with MSK conditions and provided data on associations between baseline characteristics (prognostic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
144
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(174 citation statements)
references
References 25 publications
(21 reference statements)
19
144
3
1
Order By: Relevance
“…Within this review we were looking to determine predictors of functional outcome across MSK patient populations to allow for a more evidence based approach to adjustment of case-mix to take into consideration those at a higher or lower risk of a poor outcome, not to provide information on which patients respond better to which specific treatments (modifiers of treatment outcome) (Hancock et al, 2009). This review of independent predictors of MSK functional outcome largely reflects the review findings of Artus et al (2017) and of Mallen et al (2007) on prognostic factors for patients with MSK pain. Artus et al (2017) found generic predictors of a poor prognosis with strong evidence to be: widespread pain, high functional disability, and somatisation, and predictors with a moderate level of evidence to be: high pain intensity, long pain duration and a high depression/anxiety score.…”
Section: Strongmentioning
confidence: 77%
See 2 more Smart Citations
“…Within this review we were looking to determine predictors of functional outcome across MSK patient populations to allow for a more evidence based approach to adjustment of case-mix to take into consideration those at a higher or lower risk of a poor outcome, not to provide information on which patients respond better to which specific treatments (modifiers of treatment outcome) (Hancock et al, 2009). This review of independent predictors of MSK functional outcome largely reflects the review findings of Artus et al (2017) and of Mallen et al (2007) on prognostic factors for patients with MSK pain. Artus et al (2017) found generic predictors of a poor prognosis with strong evidence to be: widespread pain, high functional disability, and somatisation, and predictors with a moderate level of evidence to be: high pain intensity, long pain duration and a high depression/anxiety score.…”
Section: Strongmentioning
confidence: 77%
“…This review of independent predictors of MSK functional outcome largely reflects the review findings of Artus et al (2017) and of Mallen et al (2007) on prognostic factors for patients with MSK pain. Artus et al (2017) found generic predictors of a poor prognosis with strong evidence to be: widespread pain, high functional disability, and somatisation, and predictors with a moderate level of evidence to be: high pain intensity, long pain duration and a high depression/anxiety score. Evidence for no association was also found for: low education (strong), pain medications (moderate) and older age and gender (weak).…”
Section: Strongmentioning
confidence: 77%
See 1 more Smart Citation
“…However, recent cohort studies and systematic reviews have highlighted similarities in symptom trajectories and identified generic prognostic factors across different regional musculoskeletal pain problems (e.g. [6, 29, 30]). This is supported by our findings from objective 1, confirming the prognostic value of short-term changes in pain for predicting long-term disability outcomes in both back and shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of some generic prognostic factors for musculoskeletal conditions prevalent in primary care has been presented, identifying high pain severity, multisite pain, baseline disability, longer pain duration, and older age as potential prognostic factors for disability across pain sites [15, 16]. However, there is limited confidence in the results.…”
Section: Introductionmentioning
confidence: 99%